Mobile Application Design: Caries Health Care for Children - Leon-Ayala, Ricardo; Andrade-Arenas, Laberiano (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Tooth decay is a problem that occurs in every person. However, children are the most vulnerable due to their diet, the consumption of foods high in sugar and poor oral hygiene. Due to this problem, the design of a mobile application was developed with the objective of preventing tooth decay in children, encouraging good oral hygiene habits in children. The mobile application basically teaches the child with the help of 3D modeling the correct way to brush his or her teeth. In addition, of using the smartphone camera to capture a photograph of the teeth. In this way it performs the analysis applying artificial intelligence to diagnose if the patient presents symptoms of caries. Also, creates a dependency of the child on the application each time he/she brushes correctly. The application provides bonuses for progressing and unlocking new interactive features; this way, attention is captured and a good habit is maintained. The agile Scrum methodology was used because it presents an orderly structure and allows adaptability. Also, offers a wide variety of graphical tools and strategies capable of displaying information in a structured way.